Treasure [videorecording (DVD)] - Heinz, Julia von; Dunham, Lena, 1986-; Fry, Stephen, 1957-; Zamachowski, Zbigniew; Brett, Lily, 1946- (FilmNation, 2024)
Journalist Ruth and Edek, her charmingly stubborn Holocaust survivor father, take a journey to his homeland, Poland, in the 1990s. While Ruth seeks to uncover her family's past, Edek has his own agenda.